Numerical simulation of blunt thoracic trauma followed by aortic rupture - Carrasco-Hernández, Francisco (2017)
Blunt thoracic trauma followed by aortic rupture (BTAR), is a unique injury to the aorta (which is the main output of blood from the heart). BTAR could be explained as a compression of the rib cage, (produced by a trauma to the chest), which affects the internal organs and injure the aorta in a specific spot. This thesis work will analyze the mechanism of this injury.